Sperm-dependent parthenogens delay the spatial expansion of their sexual hosts - Janko, K; Eisner, J (Journal of theoretical biology, 2009)
It has been known for long time that asexual organisms may affect the distribution of sexual taxa. In fact, such phenomenon is inherent in the concept of geographical parthenogenesis. On the other hand, it was generally hypothesized that sperm-dependent asexuals may not exercise the same effect on related sexual population, due to their dependence upon them as sperm-donors. Recently, however, it became clear that sperm-dependent asexuals may directly or indirectly affect the distribution of their sperm-hosts, but rather in a small scale. No study addressed the large-scale biogeographic effect of the coexistence of such asexuals with the sexual species. In our study we were interested in the effect of sexual-asexual coexistence on the speed of spatial expansion of the whole complex. We expand previously published Lotka-Volterra model of the coexistence of sexual and gynogenetic forms of spined loach (Cobitis; Teleostei) hybrid complex by diffusion. We show that presence of sperm-dependent parthenogens is likely to negatively affect the spatial expansion of sexuals, and hence the whole complex, compared to pure sexual population. Given that most of the known sperm-dependent asexual complexes are distributed in areas prone to climate-induced colonization/extinction events, we conclude that such mechanism may be an important agent in determining the biogeography of sexual taxa and therefore requires further attention including empirical tests.
Keywords: Cypriniformes; spermie; máloostní; Population Dynamics; partenogeneze; Parthenogenesis; Male; Spermatozoa; Animals; Female; biologické modely; mužské pohlaví; ženské pohlaví; populační dynamika; zvířata; Models, Biological